The Image of the Feminist Movement in the Field of Brands: An Analysis of the Paradigmatic Case of Grrrl Clothing - Fernández Rincón, Antonio Raúl; Hernández Gómez, Onésimo Samuel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The inclusion of the feminist movement in the field of brands faces the risk of commodification of its discourse and therefore of denaturalization of its claims. We analyze the communication of the brand Grrrl Clothing and reflect on the incorporation of feminist precepts in its discourse throughout 239 Instagram posts between 2015 and 2024 through the standard structuralist method. Far from purplewashing maneuvers we evidenced an effort to build a sisterhood of women with a high degree of commitment and alignment with the demands of the third wave of feminism.